Genomic comparison of virulent and non‐virulent Streptococcus agalactiae in fish. Issue 1 (15th November 2014) - Delannoy, C M J; Zadoks, R N; Crumlish, M; Rodgers, D; Lainson, F A; Ferguson, H W; Turnbull, J; Fontaine, M C
Abstract: Streptococcus agalactiae infections in fish are predominantly caused by beta‐haemolytic strains of clonal complex (CC) 7, notably its namesake sequence type (ST) 7, or by non‐haemolytic strains of CC552, including the globally distributed ST260. In contrast, CC23, including its namesake ST23, has been associated with a wide homeothermic and poikilothermic host range, but never with fish. The aim of this study was to determine whether ST23 is virulent in fish and to identify genomic markers of fish adaptation of S. agalactiae . Intraperitoneal challenge of Nile tilapia, Oreochromis niloticus (Linnaeus), showed that ST260 is lethal at doses down to 10 2  cfu per fish, whereas ST23 does not cause disease at 10 7  cfu per fish. Comparison of the genome sequence of ST260 and ST23 with those of strains derived from fish, cattle and humans revealed the presence of genomic elements that are unique to subpopulations of S. agalactiae that have the ability to infect fish (CC7 and CC552). These loci occurred in clusters exhibiting typical signatures of mobile genetic elements. PCR‐based screening of a collection of isolates from multiple host species confirmed the association of selected genes with fish‐derived strains. Several fish‐associated genes encode proteins that potentially provide fitness in the aquatic environment.